ESG: Research Progress and Future Prospects - Ting-Ting Li (MDPI AG, 2021)
The sustainable development of the global economy and society calls for the practice of the environmental, social and governance (ESG) principle. The ESG principle has been developed for 17 years following its formal proposal in 2004. Countries around the world continue to promote the coordinated development of the environment, society, and governance in accordance with the ESG principle. In order to review and summarize ESG research, this study takes the literature related to ESG research as the research object and presents the cooperation status, hot spots, and trends of ESG research with the help of the literature analysis tool CiteSpace. On the basis of quantitative analysis results, this study presents an examination and comprehensive summary of progress in the research into ESG combined with a systematic literature review. This includes the theoretical basis of ESG research, the interaction between the dimensions of ESG, the impact of ESG on the economic consequences, the risk prevention role of ESG, and ESG measurement. Based on the systematic summary of research progress, this paper further refines the characteristics of ESG research, reveals the shortcomings of ESG research, and propose a focus for ESG research in the future in order to provide a reference for academic research and the practice of ESG.